Kebijakan Kawasan Tanpa Rokok: Peluang dan Hambatan - Juanita Juanita (Center for Health Policy and Management, 2012)
Background: Currently, there are 1.2 billion smokers in the world, 80 percent of whom live in low-income countries and medium. Without prevention efforts in reducing cigarette con- sumption, the WHO predicts in 2025 the number of smokers will rise to 1.6 billion. Indonesia is the fifth in the world in the consumption of cigarettes, and a third in the number of smokers has a number of cigarette factories in the world. Objec- tive: This paper aims to analyze the Smoking Free Area Policy currently how the opportunities and threath in implementation. Methods: The study on the article of smoking free area policy in America and Indonesia Results: Although the smoking problem in Indonesia is quite alarming, but the commitment of relevant government regula- tions cigarette still weak and ambiguous. It can be seen from the lack of regulations or laws that expressly and strictly regu- lates the cigarette. Regulatory control of cigarettes in various countries managed to protecting non-smokers, increase smok- ing cessation and reduce tobacco consumption.In Health Law No. 36/2009 expressly stated that the local government shall establish Smoking Free Area Policy KTR) in the region. KTR is a room or arena are otherwise prohibited for production, sales, advertising, promotions, or the use of cigarettes. However, at present, of 497 districts / cities in Indonesia, only a minority (22 regencies / cities) which has implemented the relevant regula- tions KTR . Conclusion: There is a variety of constraints at the national level in implementing the No Smoking Zone Policy to respond by local governments to implement local policies such as local regulations, it is mainly for areas that are not producing to- bacco, clove and tobacco industry has, since the only areas will be impacted negative effects of smoking behavior of its citizens. Latar belakang: Saat ini terdapat 1,2 miliar perokok di dunia, 80 persen di antaranya tinggal di negara-negara berpendapatan rendah dan sedang. Tanpa adanya upaya pencegahan dalam pengurangan konsumsi rokok, maka WHO memprediksi pada tahun 2025 jumlah perokok akan meningkat menjadi 1.6 miliar. Indonesia berada pada posisi kelima di dunia dalam konsumsi rokok, ketiga dalam jumlah perokok dan memiliki jumlah pabrik rokok terbanyak di dunia. Tujuannya adalah untuk menganalisis Kebijakan Kawasan Tanpa Rokok yang ada saat ini bagaimana peluang dan hambatan penerapannya. Metode: Kajian terhadap artikel kebijakan kawasan tanpa rokok yang ada di Amerika dan di Indonesia Hasil: Walaupun permasalahan merokok di Indonesia cukup mengkhawatirkan, namun komitmen pemerintah terkait regulasi rokok masih lemah dan bersifat mendua. Hal ini dapat dilihat dari belum adanya peraturan ataupun undang-undang yang tegas dan ketat mengatur soal rokok. Regulasi pengendalian rokok di berbagai negara berhasil melindungi mereka yang bukan perokok, meningkatkan penghentian merokok dan mengurangi konsumsi rokok. Dalam UU Kesehatan Nomor 36/2009 secara tegas dinyatakan bahwa pemerintah daerah wajib menetapkan Kawasan Tanpa Rokok (KTR) di wilayahnya. KTR adalah ruangan atau arena yang dinyatakan dilarang untuk kegiatan produksi, penjualan, iklan, promosi, ataupun penggunaan rokok. Namun, saat ini, dari 497 kabupaten/kota yang ada di Indonesia, hanya sebagian kecil (22 kabupaten/kota) yang telah menerapkan perda terkait KTR. Kesimpulan: Adanya berbagai kendala di tingkat pusat dalam menerapkan Kebijakan Kawasan Tanpa Rokok dapat direspon oleh pemerintah daerah dengan menerapkan kebijakan lokal berupa peraturan daerah, hal ini terutama bagi daerah yang bukan penghasil tembakau, cengkeh dan tidak mempunyai industri rokok, karena daerah hanya akan mendapat dampak negatif dari perilaku merokok warganya.